The cover story effect : investors’ reactions to cover stories and the impact on share price - De la Port, Dian (University of Pretoria, 2013)
The objective of this study was to analyse the impact of business magazine cover stories, albeit positive, neutral or negative, on the share price of the featured company. Two of the aspects of investment finance are rational behaviour and efficient markets. Both of these concepts were explored to understand why a cover story would have an impact on a company share price. Causal research was conducted to analyse the correlation between a magazine cover story and the featured company’s share price. The cover stories were collected form the Financial Mail and Finance Week archives. The holding period returns were calculated and compared to zero to analyse whether there was any momentum or contrarian signals. The holding period returns were also adjusted for that of the average of the resources index (J258) to ascertain whether the returns were abnormal or not. The results have shown that in some instances, such as with neutral cover stories, the markets show strong signs of efficiency. The results of positive cover stories showed these to be momentum indicators, however when the results were adjusted for the resource index, many the positive returns dissipated. Negative cover stories had the strongest results, where after the cover story there were clear contrarian signals. Most of the companies stopped showing negative returns. Copyright === Dissertation (MBA)--University of Pretoria, 2010. === Gordon Institute of Business Science (GIBS) === unrestricted